Improvement on rooting quality of Jatropha curcas using indole butyric acid (IBA). - Abdullah, Thohirah Lee; Abdullah, Nur Ashikin Psyquay; N. A. P , Abdullah; O, Mohd Khidir (INSInet Publication, 2009)
The effects of indole-3-butyric acid (IBA) concentrations and three types of cutting (softwood,semi hardwood and hardwood) on root performance of Jatropha curcas L. cuttings were investigated. Two experiments were conducted where in experiment 1, conducted on July 2007, the hardwood cutting gave the highest mean value for root dry weight (0.2g), number of roots (22) with percentage of rooted cuttings (56%) compared to the one using softwood cutting. 10, 000 mg/L IBA gave the highest mean value for root length (13.6cm), number of roots (28), percentage of rooted cuttings (74%) with root dry weight (0.5g). In experiment 2, conducted on January 2008, the hardwood cutting once again gave the highest mean value for root length (12.1cm) and root dry weight (0.4g). The greatest root number (59) was obtained at 20, 000 mg/L. There was no significant effect on percentage of rooted cuttings, root dry weight, root length and rootball diameter. The histological studies showed that adventitious roots were originated directly from the endodermis. The root primordial started to develop on day 8 and emerged through the epidermis after day 11.